2018
DOI: 10.12659/msm.908927
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Protects Against Palmitate-Induced Apoptosis in Tubular Epithelial Cells by Promoting Fatty Acid Oxidation

Abstract: BackgroundIncreased lipid accumulation in renal tubular epithelial cells (TECs) contributes to their injury and dysfunction and progression of tubulointerstitial fibrosis. Berberine (BBR), a natural plant alkaloid isolated from traditional medicine herbs, is effective in lowing serum lipid, and has a protective effect on chronic kidney disease (CKD) with dyslipidemia, including diabetic nephropathy. The aim of this study was to investigate the effect of BBR on palmitate (PA)-induced lipid accumulation and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…In the present study, BBR supplementation in the HL diet up-regulated the hepatic expressions of lpl, cpt1a and hsl, indicating that BBR could improve lipolysis and fatty acid β-oxidation in liver. Consistent with the present study, enhanced fatty acid oxidation by BBR supplementation was also reported in blunt snout bream (15,49,55) , obese rats (42) and in vitro (16,56) .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, BBR supplementation in the HL diet up-regulated the hepatic expressions of lpl, cpt1a and hsl, indicating that BBR could improve lipolysis and fatty acid β-oxidation in liver. Consistent with the present study, enhanced fatty acid oxidation by BBR supplementation was also reported in blunt snout bream (15,49,55) , obese rats (42) and in vitro (16,56) .…”
Section: Discussionsupporting
confidence: 92%
“…Studies have been conducted to explore the role of FAO in apoptosis and its related mechanisms. It has been reported that berberine treatment reversed palmitate‐induced apoptosis in renal tubular epithelial cells by promoting FAO 38 . Yao et al found that LC supplementation in endothelial cells accelerated FAO and attenuated apoptosis caused by hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that berberine exerts its neuroprotective effect by upregulating PPARα protein levels in cells [22]. Yu et al [23] reported that berberine is a potential activator of PPARα.…”
Section: Discussionmentioning
confidence: 99%